The effect of the analogy strategy in enhancing the skill performance of some basic basketball skills (Texas Journal of Medical Science, 2022)
The objective of this study is to see how using the analogy method might help middle school students master some basic basketball abilities. The researchers designed two equal groups with pre and post observations using the experimental technique because of its relevance and the nature of the study. The research community included students of the second grade average in the middle school of Sons of Iraq / Kirkuk governorate. As for the research sample, it consisted of (40) students, The divided into two groups equally with (20) students for each group. After conducting the homogeneity and equivalence of the experimental and control groups, the researchers proceeded to invest this strategy in building (12) educational units of the Ministry of Education curriculum for the physical education lesson for the intermediate stage. The analogy strategy is a strategy based on comparing and simulating the concepts to be learned by students with those familiar and available in their previous knowledge structure. The researchers conducted the pre and post tests and in between the main research experiment. For data processing, a statistical program (SPSS) was used. After analyzing and discussing the results, the researchers concluded that the analogy strategy has a significant impact on learning some basic basketball skills for middle school students. The two research groups were superior in the post tests compared to the post-tests in the skill performance test for some basic skills (passing, dribbling, and shooting) in basketball, as well as the experimental group outperforming the control group in the results of the post test of the skill performance of some basic skills (passing, dribbling, and shooting) in basketball. The researchers recommended the necessity of urging physical education teachers to use the analogy strategy in teaching and teaching basketball skills.